VirtualCom: a simulation model for eco‐evolutionary community assembly and invasion. Issue 6 (21st April 2015) - Münkemüller, Tamara; Gallien, Laure
Summary: What is the relative importance of environmental filtering and competition in community assembly and invasion? At large spatial scales and for species‐rich systems, this question can be answered by studying functional and phylogenetic diversity patterns. The greater availability of community composition surveys, functional trait data bases and/or phylogenies from across a wide range of ecosystems has led to a significant increase in studies based on the analysis of diversity patterns. However, the underlying conceptual and methodological assumptions have recently been put into question, requiring rigorous evaluation of their reliability. In order to test these underlying assumptions, we need to be able to compare diversity patterns with their true underlying processes. For empirical data, we usually do not know these underlying processes, but for virtual data generated by simulation models, this information is available. Using two illustrative examples, we introduce VirtualCom, a simulation model that generates such data sets. Integrating both ecological and evolutionary processes, VirtualCom simulates the evolution of the pool of regionally occurring species, the process‐based assembly of native communities and the invasion of novel species into native communities. The model provides functionalities for a variety of processes. Most importantly, in the simulation of the species pool, different trait evolution models allow the generation of clustered and random trait distributions in the phylogeny (resulting in varying strength of phylogenetic signal). Additionally, when the species assemble from the species pool into local communities based on their trait values, the relative strength of environmental filtering and competition can be set independently. By offering possibilities for a broad range of simulation‐based modelling experiments, VirtualCom is a simple and readily usable tool that will help to resolve theoretical and methodological issues in community ecology.